HUMANISTIC EDUCATION IN LANGUAGE LEARNING - Susrawan I Nyoman Adi; I Made Sutajaya; I Wayan Suja (Lembaga Penelitian dan `Pengabdian Kepada Masyarakat (LPPM), 2023)
Humanistic education emphasizes the importance of understanding each individual as a human being. A humanist educator treats his students according to their potential. Humanistic education can provide direction to all components of learning. All educational components are directed at forming an ideal human being, namely a human being capable of achieving self-actualization. This research uses qualitative research methods where data is collected by examining various sources related to humanistic education. Data was collected through literature study interviews with teachers and students selected as research subjects. The collected data was analyzed descriptively to reveal teachers' and students' perceptions of the importance of humanist education in Indonesia. This research shows that humanist education is necessary to improve students' competence and character. This research implies that it is necessary to improve the implementation of humanist education in all educational institutions.